Routine pretreatment patient‐specific IMRT QA (PS‐IMRT‐QA) should be discontinued and replaced with a real‐time on‐board beam monitoring system (BMS). Issue 9 (11th July 2021) - Zygmanski, Piotr; Halvorsen, Per
Overview: In an era of automated measurements and analysis, the time and resource intensive process of dosimetric plan verification for intensity modulated radiation therapy treatments would seem to be ripe for improvement. In this Point‐Counterpoint contribution, the authors debate benefits of methods both hypothetical and established. I offer thanks to our contributors and note that they are writing in the classic style of a debate, the opinions that they argue may or may not reflect their personal views."